(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the role and significance of economic and socio-political values in shaping the spiritual identity of individuals within the context of the ongoing renewal in Uzbekistan. As the country undergoes dynamic reforms aimed at building a modern and just society, the formation of a morally grounded personality has become one of the key priorities of national development. The paper analyzes how economic progress and political stability intersect with spiritual education, national values, and ethical behavior, ultimately contributing to the cultivation of socially responsible and ideologically conscious citizens. The study also emphasizes the necessity of integrating traditional values with contemporary socio-political norms to ensure a balanced and holistic development of the individual in the New Uzbekistan.